P. Louvre E 7856 C: A Possible Memorandum about Tax Payment from the Eisenlohr Lot - Heel, Koenraad Donker van (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
First publication of P. Louvre E 7856 C, a documentary fragment from the archive of Djekhy & Son (abnormal hieratic and early demotic P. Louvre E 7832-7861, bought together with Ptolemaic demotic P. Louvre E 7862), which shows both abnormal hieratic and early demotic traits. It was most probably written in the reign of Amasis, and may have been a receipt for the payment of the tax of the overseer of the necropolis ( HD mr-X#s.t ) or – perhaps more likely – a memo about the payment of this (or another) tax.